“TRANSHUMANIZATION” OF MODERN EDUCATION - G. L. ILYIN (Высшее образование в России)
The paper defines the concept of transhumanism, which denotes transition beyond the bounds of humanism and bears in mind utterly new human beings. The author views the prospects of modern education through the optics of transhumanism project, describes the changes in education on the background of explosive growth of NBICS-technologies. NBICS combine nanotechnology, biotechnology, IT, cognitive and social sciences, genetic engineering, stem cells, and cloning. These research areas converge and create a cumulative effect. One of the risks and threats of the technology growth is creation of the community of humanoid robots and “service people”. Information society changes radically the conditions of learning and teaching owing to multiple sources of information and communication facilities. Internet becomes a part of learning process and at the same time causes a discord between school knowledge and information and leads to historical disorientation in society. This is one of the signs of dehumanization of education. The second feature of education in the light of transhumanism conception is the problem of knowledge value. Now there are two scales for evaluation of knowledge – cultural and actual. The second scale uses utility and applicability as a criterion. It follows that mass accessible education is ineffective and there is a need in institutional elite education. The third feature of modern education in the context of transhumanism is an emergence of lifelong education and its separation from institutional teaching. Lifelong education ceases to be externally organized process affecting a learner and becomes a personal affair manifesting individual’s activity and self-development. Mass education is based on learning and teaching whereas elite education is based on education. The paper comes to a conclusion that this is a period of so called “transhumanistic turn” of domestic education which indicates its dehumanisation and the loss of former values.